Role of plant secondary metabolites in combating pest induced stress in brinjal (Solanum melongena L.) - Talukder, Pratik; Dutta, Debankita; Ghosh, Elija; Bose, Indrani; Bhattacharjee, Sourish (Journal of Environmental Engineering and Landscape Management, 2021)
Brinjal or eggplant (Solanum melongena L.) is known as a vegetable of diet because it contains high moisture and low calorific value. It is also a good source of antioxidants and phytonutrients. Brinjal is widely grown in the South and South-East Asian countries and is the second most important vegetable in India. It belongs to the Solanaceae family. Shoot and fruit borer (Leucinodes orbonalis) pest of brinjal is the most widespread one and it has the ability to affect any of the developmental stages of brinjal. Plants and their insect herbivores have had a long and intimate evolutionary association that has resulted in many complex interactions mediated by specialized plant metabolites like phenolics, alkaloids, terpenoids, cyanogenic glycosides etc. Frequent and excessive use of insecticides has become a common practice now which only increases the probability of resistance development and resurgence of pest. Hence to develop an effective approach to combat this pest understanding of its feeding mechanism and chemistry of its interaction with the fruit is necessary. The importance of the secondary metabolites in the field of chemical biology and in pest management is discussed in this study.